Competing Nationality Politics Targeting German Communities at the Hungarian-Romanian Border Zone after the Great War - Szilágyi, Levente (Ethnographica et Folkloristica Carpathica, 2020)
In my study, I focus on the events that took place in the short period after the Great War ended (1918) and before the consolidation of Romanian power in the Hungarian-Romanian Border Commission (1922) from the point of view of the artificially created ethnic category: the Satu Mare Swabians or Sathmar Swabians. The historiography related to the “ethnographic” aspects of these events have appeared multiple times and in several contexts and forms in the years since. However, the question of ethnicity has not arisen in relation to the population of German descent, but rather in relation to the Hungarian-speaking Greek Catholic communities of Romanian and Rusyn/Ruthenian origin who were treated by the Romanian side as Magyarized Romanians. Following this example, the Romanians later began to collect data on the Magyarized Germans, which they then presented to the Border Commission. Germans living in the territory witnessed a strong competition between identity politics and discourse supported by rival Hungarian and Romanian states. One of the key features of this rivalry was the intensive propaganda activity promoted by both the Romanian and the Hungarian authorities to gain territories to the detriment of the other.